2020
DOI: 10.3389/fsufs.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-Dense Orange-Fleshed Sweetpotato: Advances in Drought-Tolerance Breeding and Understanding of Management Practices for Sustainable Next-Generation Cropping Systems in Sub-Saharan Africa

Abstract: Low et al. Drought-Tolerant Orange-Fleshed Sweetpotato Early maturing cultivars (< 4 month growing period) that escape drought but also serve humid environments with small landholding size per capita; and (2) Medium maturing (4-6 month growing period) cultivars that avoid drought, are drought tolerant and exhibit continuous root formation. Increasing commercialization of the crop and climate change will drive demand, and the willingness of farmers to invest in improved sweetpotato crop management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 132 publications
0
61
0
Order By: Relevance
“…Sweetpotato ( Ipomoea batatas (L) Lam) is of increasing importance for food and nutrition security in sub‐Saharan Africa (SSA; Low et al ., 2020). It is a versatile climate‐resilient crop because it is easily propagated and can grow with few external inputs on degraded soils under a range of rainfall patterns (Mukherjee et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sweetpotato ( Ipomoea batatas (L) Lam) is of increasing importance for food and nutrition security in sub‐Saharan Africa (SSA; Low et al ., 2020). It is a versatile climate‐resilient crop because it is easily propagated and can grow with few external inputs on degraded soils under a range of rainfall patterns (Mukherjee et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From a physiological point of view, drought tolerance encompasses all mechanisms that enable plants to avoid or tolerate dehydration, such as maintenance of cell turgor and water uptake, and reduction of water loss, among others (Fischer and Maurer, 1978;Turner, 1986;Turner, 1997). In sweetpotato, several physiological traits have been used for screening drought tolerant genotypes such as chlorophyll concentration (Mbinda et al, 2018;Mbinda et al, 2019), canopy cover (Laurie et al, 2014), leaf temperature (Laurie et al, 2014;Rukundo et al, 2017;Low et al, 2020), and 13 C discrimination (Low et al, 2020). The latter has been reported as one of the most accurate criteria for selecting drought tolerant genotypes (Tuberosa, 2012;Low et al, 2020) since it is a good indicator of stomatal conductance (Condon et al, 2004), water use efficiency (Turner, 1997), and photosynthetic performance (Jefferies and Mackerron, 1997;Dawson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Gomo et al (2014) concerning SIS in South Africa reported that water productivity is higher as the distance from the main canal increase. The sweet potato is a drought-tolerant, short maturing crop (Low et al, 2020). Hence, the production of sweet potato in plots that are far away from the main irrigation canal is more viable as it has smaller water requirements compared to other crops grown in the scheme.…”
Section: Discussionmentioning
confidence: 99%